Biotransformation of Daidzein, Genistein, and Naringenin by Streptomyces Species Isolated from High-Altitude Soil of Nepal - Lasata Shrestha; Bishnu P. Marasini; Suman Prakash Pradhan; Rajib Kumar Shrestha; Suraj Shrestha; Kamal Prasad Regmi; Bishnu Prasad Pandey (International Journal of Microbiology, 2021)
Flavonoids have achieved widespread importance in pharmaceutical, food, and cosmetics industries. Furthermore, modification of these naturally occurring flavonoids to structurally diverse compounds through whole cell biotransformation with enhanced biological activities has numerous biotechnological applications. The present study investigated the biotransformation potential of Streptomyces species isolated from a high-altitude-soil sample towards selected flavonoid molecules. The biotransformed metabolites were confirmed by comparing the HPLC chromatogram with authentic compounds and LC-MS/MS analysis. Of these isolates, Streptomyces species G-18 (Accession number: MW663767.1) catalyzed isoflavone molecules daidzein and genistein to produce hydroxylated products at 24 h of reaction condition in a whole cell system. The hydroxylation of daidzein (4′,7-dihydroxyisoflavone) was confirmed at 3′-position of the B ring to produce 3′,4′,7-trihydroxyisoflavone. In addition, Streptomyces species G-14 (Accession number: MW663770.1) and Streptomyces species S4L (Accession number: MW663769.1) also revealed the transformation of daidzein (4′,7-dihydroxyisoflavone) to hydroxy daidzein at a distinct position than that of G-18 isolates, whereas thee Streptomyces species S4L reaction mixture with naringenin as a substrate also revealed the hydroxylated product. Our results demonstrated that microorganisms isolated from different ecological niches have broad application.